The Influence of Transformational Leadership Style and Work Motivation on the Performance of PT Tara's Outsourced Employees in the Maintenance Work Unit of PT Bukit Asam Kertapati Pier Unit - Oktariadi, Satria; Widiyanti, Marlina; Yusuf, Muhammad; Hanafi, Agustina (Riviera Publishing, 2024)
This study was conducted to determine the influence of transformational leadership style and work motivation on the performance of PT Tara's outsourced employees in the PT Bukit Asam Dermaga Kertapati Unit maintenance work unit. The population and sample in this study are all PT Tara's outsourced employees in the PT Bukit Asam Kertapati Pier Unit maintenance work unit in 2023-2024, with as many as 33 employees using the census method. The results of multiple linear regression analysis show that transnational leadership style and work motivation have a positive and significant effect on employee performance. In a transformational leadership style, it is hoped that the role of the boss can provide opportunities for employees to provide opinions. Work motivation: it is hoped that the boss can provide fair input to employees so that fellow employees can establish good relationships.